PRZEKAZYWANIE NIERUCHOMOŚCI ZBĘDNYCH POZA RESORT OBRONY NARODOWEJ - Murach, Marta (Civitas et Lex, 2014)
Resource military estate is diverse in terms of process of real estate management. This paper analyzes the process of transferring real estate military that have become permanently useless for the Ministry of Defense. As a result of this legal tool is implemented public purpose, which is to protect the financial restructuring activities of the Polish army. This paper shows the legal basis, individual competence of the military authorities and procedures of transferring military real estate outside the Ministry of Defense.